Construction of China cardiovascular health index - Yingying Jiang; Fan Mao; Yichong Li; Jing Liu; Yan Zhang; Yong Jiang; Dong Zhao; Weiwei Chen; Stephen Nicholas; Yong Huo; Junbo Ge; Linhong Wang; et al. (BMC, 2018)
Abstract Background Cardiovascular disease (CVD) is not only the primary cause of death in developed western countries, but also its disease burden is increasing in China. The purpose of constructing population cardiovascular health index is to monitor, compare and evaluate disease burden, influencing factors and prevention and control levels of Chinese population cardiovascular disease in order to provide evidence to improve population cardiovascular health. Methods This study collected multi-source data and constructed China Cardiovascular Health Index (CHI) using literature review, questionnaire surveys, Delphi method and Analytical Hierarchy Process (AHP) model. Results China CHI system included 52 indices of 5 dimensions, which were prevalence status of CVD, exposure of risk factors, prevention and control of risk factors, treatment situation and public health policy and service ability. The weights of 5 dimensions from high to low were successively prevention and control of risk factors 0.3656, prevalence status of CVD 0.2070, treatment situation 0.1812, public health policy and service ability 0.1458, and exposure of risk factors 0.1004. Conclusion China CHI is a comprehensive evaluation system raised to effectively control the prevalence of CVD. In the future, we should strengthen and improve CVD monitoring and big data usage, to ensure these indices to reflect the practical situations and to become utility of controlling CVD.